The wishing game ebook A novel. - Shaffer, Meg (2023)
NATIONAL BESTSELLER • Years ago, a reclusive mega-bestselling children’s author quit writing under mysterious circumstances. Suddenly he resurfaces with a brand-new book and a one-of-a-kind competition, offering a prize that will change the winner’s life in this absorbing and whimsical novel. “Clever, dark, and hopeful . . . a love letter to reading and the power that childhood stories have over us long after we’ve grown up.”—V. E. Schwab, #1 New York Times bestselling author of The Invisible Life of Addie LaRue A BEST BOOK OF THE YEAR: Washington Post, She Reads, Bookreporter Make a wish. . . . Lucy Hart knows better than anyone what it’s like to grow up without parents who loved her. In a childhood marked by neglect and loneliness, Lucy found her solace in books, namely the Clock Island series by Jack Masterson. Now a twenty-six-year-old teacher’s aide, she is able to share her love of reading with bright, young students, especially seven-year-old Christopher Lamb, who was left orphaned after the tragic death of his parents. Lucy would give anything to adopt Christopher, but even the idea of becoming a family seems like an impossible dream without proper funds and stability. But be careful what you wish for. . . . Just when Lucy is about to give up, Jack Masterson announces he’s finally written a new book. Even better, he’s holding a contest at his home on the real Clock Island, and Lucy is one of the four lucky contestants chosen to compete to win the one and only copy. For Lucy, the chance of winning the most sought-after book in the world means everything to her and Christopher. But first she must contend with ruthless book collectors, wily opponents, and the distractingly handsome (and grumpy) Hugo Reese, the illustrator of the Clock Island books. Meanwhile, Jack “the Mastermind” Masterson is plotting the ultimate twist ending that could change all their lives forever. . . . You might just get it.